STUDENTS’ KNOWLEDGE AND ATTITUDES TOWARDS INCLUSION IN COLLEGE - Laurensia Aptik Evanjeli (LPMPP Universitas Negeri Yogyakarta, 2021)
Students’ knowledge and attitudes towards individuals with special needs contribute to the realization of inclusion. This study aims to describe the graduate students’ knowledge and attitudes towards graduate students with special needs. The number of participants in this study was 130 (37.14% response rate) with an age range of 18-28 years. Correlation analysis, t-test analysis, and ANOVA was conducted to determine the relationship between student knowledge and their attitudes, and comparison of the demographic data. The results showed that there was a positive relationship between knowledge and attitudes towards inclusion but the correlation between knowledge and attitudes towards inclusion tended to be weak. The low correlation coefficient between knowledge and attitudes indicates that knowledge about disabilities is not the main factor determining student attitudes towards inclusion. The experience of interacting with individuals with special needs did not significantly contribute to knowledge and attitudes towards inclusion. The reported interactions with individuals with special needs are in the form of very close and close relationships such as relation with family members, close enough relationships such as relation with colleagues or staff, and acquaintances such as relation with neighbors.